MIGUEL GUITART - Behind Architectural Filters. Phenomena of Interference - Labarta Aizpún, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Miguel GuitartBehind Architectural Filters. Phenomena of InterferenceNew York: Routledge, 2022. 302 pp. Hardcover. Language: English. 36,26 €ISBN: 978-1-032-07748-2